1982
DOI: 10.1029/jc087ic11p08839
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide in seawater (Atlantic Ocean)

Abstract: In 1978–1980, measurements of dissolved carbon monoxide in seawater were carried out during three ship expeditions in the northern and southern Atlantic Ocean, covering an area between 53°N and 35°S. Measurements in surface water were performed by a continuously working equilibration technique that allowed for the determination of small and rapid variations of the dissolved CO. Carbon monoxide concentrations in the water body increased toward the sea surface, there reaching saturation factors of up to 50 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
130
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 28 publications
15
130
0
Order By: Relevance
“…This process is of particular importance for those stations located at latitudes south of 30° S where the land surface and thus the continental C O production is negligible. The oceanic CO source strengths, either by direct CO emission from the oceans (Conrad et al, 1982) or by CO formation of hydrocarbons emitted from the ocean (Lamontagne et al, 1974(Lamontagne et al, , 1975Singh et al, 1978;Rudolph et al, 1982) are very small if compared with the total C O source strengths. Thus, the "excess CO" to balance the photochemical production and destruction of C O at 35"s must be advected from northerly latitudes.…”
Section: Hcho Chooh)mentioning
confidence: 99%
See 1 more Smart Citation
“…This process is of particular importance for those stations located at latitudes south of 30° S where the land surface and thus the continental C O production is negligible. The oceanic CO source strengths, either by direct CO emission from the oceans (Conrad et al, 1982) or by CO formation of hydrocarbons emitted from the ocean (Lamontagne et al, 1974(Lamontagne et al, , 1975Singh et al, 1978;Rudolph et al, 1982) are very small if compared with the total C O source strengths. Thus, the "excess CO" to balance the photochemical production and destruction of C O at 35"s must be advected from northerly latitudes.…”
Section: Hcho Chooh)mentioning
confidence: 99%
“…Potential sources of this "excess CO" are technological processes (such as automobiles, industry, home-heating), burning of biomass, photochemical oxidation of hydrocarbons as well as CO emissions by plants, CO formation in the ocean and transport of CO from the northern into the southern hemisphere by interhemispheric air mass exchange (Newell et al, 1974;Seiler, 1976;Seiler, 1978;Bauer et al, 1979;Logan et al, 1981;Crutzen and Gidel, 1983;Conrad et al, 1982). The source strengths of these processes in the southern hemisphere have recently been estimated to be 526-915 Tg yr-' which exceed the photochemical C O production of 302-405 Tg yr-I by a factor of about 2 (Logan et al, 1981;Crutzen and Gidel, 1983).…”
Section: Hcho Chooh)mentioning
confidence: 99%
“…Carbon monoxide emissions from live or dead plant matter are from the photodegradation or photooxidation of cellular material [55] and oceanic CO is mainly produced by the photochemical oxidation of dissolved organic matter [56,57]. The inventories of these natural sources are taken from the POET atmospheric gas inventory [58] (Table 1).…”
Section: Sources and Sinks Of Atmospheric Comentioning
confidence: 99%
“…The automated system, instrumental response and calibration standards have been previously described (Kelly-Hansen and Gammon, 1986). This data set represents the most comprehensive survey of the saturation state of CO at the sea surface to date, complementary to and more extensive than the Atlantic survey of Conrad and Seiler (1982). The major findings from this earlier work (e.g., diurnal cycle of CO in the near surface waters lagging local sunlight, correlations of observed CO supersaturation with insolation and chlorophyll and inversely with wind speed) are confirmed and refined in the present study of the North and South Pacific and Indian oceans in a variety of seasons and oceanographic regimes.…”
Section: Seattle Washington 98115mentioning
confidence: 99%
“…Recent studies have shown that the marine photochemical formation rates of carbon monoxide (Gammon and Kelley, 1988;Conrad et al, 1982) and carbonyl sulfide vary greatly in different types of sea water. Other studies have shown that sunlight-induced reaction rates of a given organic substance in various natural water samples can vary by orders of magnitude (Skurlatov et aL, 1983;Simmons and Zepp, 1986;Haag and Hoigné, 1986;Larson and Zepp, 1988).…”
Section: Introductionmentioning
confidence: 99%